2010
DOI: 10.1016/j.gaceta.2009.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Expectativas de los pacientes sobre la toma de decisiones ante diferentes problemas de salud

Abstract: Most patients wished to be listened to, informed and taken into account by their general practitioners and, to a lesser extent, wished to take decisions autonomously, especially for biomedical problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
0
2
0
2
Order By: Relevance
“…La mayoría de los participantes adoptaban un rol pasivocolaborativo o completamente pasivo en relación con la toma de decisión sobre su tratamiento, tal y como señalan los resultados encontrados en trabajos similares (Arora & McHorney, 2000;Delgado et al, 2010). Aunque en pacientes con depresión y ansiedad, algunos autores han informado de tasas de hasta el 98% de participación con un papel semi-activo o semi-pasivo (Patel & Bakken, 2010).…”
Section: Discussionunclassified
“…La mayoría de los participantes adoptaban un rol pasivocolaborativo o completamente pasivo en relación con la toma de decisión sobre su tratamiento, tal y como señalan los resultados encontrados en trabajos similares (Arora & McHorney, 2000;Delgado et al, 2010). Aunque en pacientes con depresión y ansiedad, algunos autores han informado de tasas de hasta el 98% de participación con un papel semi-activo o semi-pasivo (Patel & Bakken, 2010).…”
Section: Discussionunclassified
“…Their responses to the interviews confirm that patients with life-threatening illnesses are as concerned as other patients to have information that might help them participate in decision making, even when they do not directly ask to participate. 29,30 The participants understood that healthcare professionals needed their consent to proceed with a treatment or an intervention, and they expected to be given information that would help them understand why this had been deemed appropriate for their particular needs. In other words, they understood that completing a process of informed consent did not simply involve accepting or rejecting a professional proposal but was also an opportunity to understand that proposal.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, 360 Spanish patients underwent a questionnaire by Delgado et al The data revealed that while the majority of the interviewees wished to be heard and informed by the doctor, the patients' autonomous participation was seen as an undesired increase in their accountability. More serious diseases are also associated with an even lower wish to participate 16 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%